Changing Conditions for Local Food Actors to Operate Towards Agroecology During the COVID-19 Pandemic - Frank, Markus; Kaufmann, Brigitte; Ejarque, Mercedes; Lamaison, María Guadalupe; Nessi, María Virginia; Amoroso, Mariano Martin (Frontiers in Sustainable Food Systems, 2022)
Given the novel character of disturbances caused by the pandemic in food systems, initial studies have been conducted to stress the reinforced urgent need for food systems' transformation toward sustainability. First assessments, conducted in the early months of the pandemic, found that local food actors responded to changing production and marketing conditions by implementing alternative practices under the umbrella of agroecology. However, given the unprecedented and dynamic character of the pandemic in regional situations, and related context-specific changes caused in food system actors' operations, case studies are needed to assess in more detail under which changing conditions food actors implemented alternative practices. Moreover, the maintenance of practices as conditions normalize, and food actors' transformative potential in relation to the principles of agroecology, need further assessment. In response to these emerging issues, we provide insights into our case study research conducted during 2021 in a local food system in Argentina. The aim of this research was to study how changing conditions triggered local food actors to (re-)frame their objectives and activities regarding marketing, and to assess the relevance of agroecological principles as a means of responding to changing conditions and to unfold longer-term transitions. We identified local producer shops (n = 5) and markets (n = 4) that were established or consolidated by self-organized producer groups (SOPGs) during the first months of the pandemic. Using semi-structured interviews with SOPG members (n = 12) and qualitative content analysis, we found that alternative practices were adopted in response to different changing conditions, and new needs and opportunities for producers and consumers brought about by the pandemic. Objectives pursued, and activities undertaken by the groups revealed reactive short-term mitigation strategies, and proactive longer-term transformative objectives. The relational analysis between practices and agroecological principles showed that the principles became important means of responding to changing conditions and to unfold longer-term transitions. The cases illustrate how local food actors operationalized agroecological principles, and in turn how principles can be used to investigate the nature and potentials of food actors' alternative practices, highlighting the relevance of agroecology to co-design sustainability transitions in local food systems and to mitigate possible future crisis.